'n Geestesgesondheidsmodel vir ondersteuning van gesinslede wat moet besluit oor die onttrekking van lewensondersteunende behandeling - M. Oberholster; M. Poggenpoel; A. C. Gmeiner (AOSIS, 2003)
The aim of this research is to develop, describe, operationalise and evaluate a model as framework for meaningful support by the advanced psychiatric nurse, which will serve to support family members who are involved in the decision-making process regarding the withdrawal of life sustaining treatment, in order to promote their mental health. The paradigm of the Department of Nursing of the Rand Afrikaans University, which endorses the Theory for Health Improvement in Nursing (Randse Afrikaanse Universiteit: Departement Verpleegkunde, 200:1-16) was accepted for the purpose of this research.